Stable isotope ratio of G. sacculifer in sediment core MD99-2198 (0-125 ka) - Anastasia Zhuravleva (PANGAEA, 2021)
Stable isotope ratios in planktic foraminifera were measured every 20 cm for the upper 0-18.5 m and every 10 cm between 18.5-22 cm (revised depth). Note that the original core depth scale in core MD99-2198 was modified by excluding two intervals (10.06-10.24 m and 13.78-14.30 m), representing episodes where the core was ripped apart, as could be concluded on the basis of large increases in porosity.